2020
DOI: 10.1891/emdr-d-20-00022
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function Assessment of a Patient With PTSD Before and After EMDR Treatment

Abstract: The current case study investigates whether successful psychotherapy for posttraumatic stress disorder (PTSD) symptoms will also ameliorate cognitive deficits. We describe the treatment response of a 37-year-old woman diagnosed with post-traumatic stress disorder who received eight weeklyEMDR sessions. At pre-treatment, the patient reported emotional disturbance on the Beck Depression Inventory-II, and problems with anxiety and sleep. Testing showed high scores on the State-Trait Anxiety Inventory (STAI) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Simultaneously assessing the qualitative impact of EMDR on participants, alongside quantitative data collection, addressed the recommendation identified by Marich et al (2020), that qualitative assessments should not primarily follow or come after quantitative ones, as most existing ones had. In terms of clients' personal experiences of EMDR, qualitative findings of this study echo prior findings that EMDR treatment decreases vividness of traumatic memories (Cotter et al, 2017), increases insight about the past (Shipley et al, 2021), strengthens self-confidence (Cotter et al, 2017), increases positive emotions (Cotter et al, 2017), drives transformative change (Shipley et al, 2021), and improves cognitive functioning (Aranda et al, 2015;Camacho-Conde, 2020). Transformative change and improved cognitive functioning are expected changes related to the AIP model, which addresses treatment at the source of pathology, targeting insufficiently processed information from a disturbing event early in life (Shapiro, 2018).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Simultaneously assessing the qualitative impact of EMDR on participants, alongside quantitative data collection, addressed the recommendation identified by Marich et al (2020), that qualitative assessments should not primarily follow or come after quantitative ones, as most existing ones had. In terms of clients' personal experiences of EMDR, qualitative findings of this study echo prior findings that EMDR treatment decreases vividness of traumatic memories (Cotter et al, 2017), increases insight about the past (Shipley et al, 2021), strengthens self-confidence (Cotter et al, 2017), increases positive emotions (Cotter et al, 2017), drives transformative change (Shipley et al, 2021), and improves cognitive functioning (Aranda et al, 2015;Camacho-Conde, 2020). Transformative change and improved cognitive functioning are expected changes related to the AIP model, which addresses treatment at the source of pathology, targeting insufficiently processed information from a disturbing event early in life (Shapiro, 2018).…”
Section: Discussionsupporting
confidence: 74%
“…Uniquely, EMDR participants experienced distressing memories less clearly and vividly, and CBT participants experienced adoption of emotional regulation tools (Cotter et al, 2017). Multiple additional case studies demonstrate EMDR improving cognitive functioning, particularly related to participant's attention profile (Camacho-Conde, 2020;Aranda et al, 2015). In reviewing existing qualitative research, Marich et al (2020) identified that a number of qualitative assessments specifically followed quantitative ones, reflecting a more quantitative orientation in EMDR research.…”
Section: Emdr As a Treatment Optionmentioning
confidence: 99%
“…Our aim was to have specific studies of the main disorders that were previously described with larger samples. In fact, Nesplora Aquarium is currently being applied to various disorders in the population, as evidenced by the recent study by Camacho-Conde and Climent [43], conducted in adults with ADHD, to assess their attentional profile; a clinical case of a patient with PSTD [44]; a study based on the control of temporary disability due to common contingency in patients with minor psychiatric disorder [45]; and a recent study that examined the effectiveness of Nesplora Aquarium, evaluating participants with low and high symptoms of depression and anxiety [46]. Another limitation is the signs of cognitive deficits that are evident with aging, being more evident in subjects older than 50 years; we recognize that depressive symptoms can be predictors of visual memory deficits in middle age [96], and older anxious subjects displayed cognitive impairments in short-term memory; while older depressed patients showed executive dysfunction and more general cognitive impairments, not evident in older anxious subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Nesplora Aquarium [40] is a neuropsychological test that, through different continuous performance paradigms (CPT), evaluates attentional processes and working memory in people over 16 years of age and that has recently shown good psychometric properties related to its reliability and internal consistency values in a normative study, as well as being used in another series of studies [43][44][45][46][47][48][49]. The tool was found to have high internal consistency, and performance decreased with age, as would be expected.…”
Section: Nesplora Aquariummentioning
confidence: 99%
“…Efficacy in the child and adolescent population is studied in 8 of them (Ahmad et al, 2007;Chemtob et al, 2002;de Roos et al, 2011;Diehle et al, 2015;Jaberghaderi et al, 2004;Kemp et al al., 2010;Scheck et al, 1998;Soberman et al, 2002). In addition, there is evidence of its usefulness for the treatment of people with impaired executive functions and altered attentional processes after trauma (Camacho-Conde, 2020;Estrada, et al, 2015).…”
Section: Trauma Treatment: Emdr Therapymentioning
confidence: 99%